Wnt/beta-catenin and PI3K/Akt/mTOR Signaling Pathways in Glioblastoma: Two Main Targets for Drug Design: A Review - Shahcheraghi, Seyed H.; Tchokonte-Nana, Venant; Lotfi, Marzieh; Lotfi, Malihe; Ghorbani, Ahmad; Sadeghnia, Hamid R. (Current Pharmaceutical Design, 2020)
Glioblastoma (GBM) is the most common and malignant astrocytic glioma, accounting for about 90% of all brain tumors with poor prognosis. Despite recent advances in understanding molecular mechanisms of oncogenesis and the improved neuroimaging technologies, surgery, and adjuvant treatments, the clinical prognosis of patients with GBM remains persistently unfavorable. The signaling pathways and the regulation of growth factors of glioblastoma cells are very abnormal. The various signaling pathways have been suggested to be involved in cellular proliferation, invasion, and glioma metastasis. The Wnt signaling pathway with its pleiotropic functions in neurogenesis and stem cell proliferation is implicated in various human cancers, including glioma. In addition, the PI3K/Akt/mTOR pathway is closely related to growth, metabolism, survival, angiogenesis, autophagy, and chemotherapy resistance of GBM. Understanding the mechanisms of GBM’s invasion, represented by invasion and migration, is an important tool in designing effective therapeutic interventions. This review will investigate two main signaling pathways in GBM: PI3K/Akt/mTOR and Wnt/beta-catenin signaling pathways.
Keywords: Wnt signaling pathway